RESPONSE OF NON MUSLIM CUSTOMERS ON THE CONVERSION OF NTB BANKS TO SHARIA NTB BANKS - Dewi Sartika Nasution; Syukriati Syukriati; Urwatul Wusqo (UIN Mataram, 2021)
This study aims to determine the response of non-Muslim customers of the NTB Bank of Mataram City to the conversion of Bank NTB to Islamic Banks. The method used in this study was to distribute questionnaires to 112 respondents. The variables in this study are the knowledge of sharia banking, the attitudes of non-Muslim customers to sharia banks and the behavior of nonMuslim customers to sharia banks and conversion of NTB Banks to sharia Banks. The collected data were analyzed using multiple linear regression analysis and Pearson correlation. From the results of the analysis it was found that the three independent variables influence the formation of responses to the NTB Bank conversion. The influence given is only 33% which is influenced by the three variables and the rest is influenced by other factors. The abstract serves important purpose in summarizing the hypothesis, design, and finding of the study. The abstract isin one paragraph, it consists of a clear statement of the background of the study, purpose of the study, method and finding. It should be written concisely and coherently using academic English.It should not more than 200 words. Written with calibri size 11, single spacing, italic, andjustify alignment.